Upaya Warga Dalam Meningkatkan Pendapatan Rumah Tangga Melalui Usaha Ternak Bebek Pedaging Dusun Jigang - Ririn Fitriani; Tutut Suryaningsih (Pusat Riset dan Inovasi Nasional, 2023)
The background of this research is because at this time the development of broiler ducks is actually not very popular in our ears, but in one of the business options in the livestock sector it turns out to be quite promising with quite large economic potential. The structure of the trade of broiler ducks is now starting to be more in demand by the public, because the taste of the meat is tasty and delicious. The purpose of this study was to find out what efforts were made by breeders in Jigang hamlet to increase household income through broiler duck farming. This study uses qualitative research. Data collection techniques in this study are observation, interview, and documentation methods. The results of the study show that the efforts made by broiler duck breeders to increase their household income are by choosing quality seeds, this is intended to reduce the risk of death, then provide vaccines and vitamins, provide factory feed and alternative feed and pay attention to the condition of the cage after the harvest period. so that the cage is far from the virus and harvest at the age of the ducks 35-45 days. This is an effort that breeders can make to increase their household income. This duck livestock business is a means of making a living to change a more decent life.